Soybean Production - Actual Statement and 2020-2024 Forecast in Romania - Agatha POPESCU (Communications of International Proceedings, 2020)
The paper analyzed the dynamics of soybean cultivated area, production and yield in Romania in the period 2010 -2019 and  established the estimates of sown area and seeds output for the 2020-2024 horizon. Both the soybean cultivated surface and production registered a high development in the last decade, so that in 2019, in Romania, 158,149 ha were harvested from which there were obtained 415,942 tons of seeds, meaning 2.8 times more than in 2010. Yield had a slight increase of only 12% and accounted for 2,630 kg/ha in 2019, which proved that surface extend had a more important influence on production growth than yield. The decision to chose the quadratic trend model having the formula Y = 581.53 x2  + 6,834,4 x + 51,174 for the cultivated area and  Y = 3,841.7 x2 - 2,863,9 x  + 122,867 for production for setting up the estimates for the next five years was taken based on the results obtained for R2, 2, RMSE,  MAE, and MAPE criteria which offered  a higher accuracy. In 2024, it is expected that Romania to produce 844,291 tons soybean seeds from 284,534 ha cultivated with this crop. Farmers are interested to increase the cultivated areas and production, as a response to the subsidies offered by the EU according to its new Green CAP policy reform regulations and Danube Soya Program aiming to grow protein output from certified non GMO crops like soybean.
Keywords: Soybean production; trends; growth models; forecast; Romania